2020
DOI: 10.3390/ijerph17030848
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study Assessing Acceptability and Supply Issues of Distributing LPG Cookstoves and Gas Cylinders to Pregnant Women Living in Rural Bangladesh for Poriborton: The CHANge Trial

Abstract: Our aim was to develop a protocol for a cluster randomised controlled trial to assess the impact of liquid petroleum gas (LPG) cooking compared to usual cooking on perinatal mortality in pregnant women in rural Bangladesh. We, therefore, aimed to assess the feasibility of the planned trial and the barriers/facilitators of distributing LPG to rural households. We conducted a feasibility study in rural Bangladesh using an iterative design. We included pregnant women, their families, and local LPG stakeholders. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Bangladesh experiences cooler temperatures in November and December, which increases traditional fuel use to heat the participant’s homes, especially evident since 29 of the 30 participants kept their traditional stoves in a separate kitchen [ 45 ]. Our survey data determined stove stacking was common as participants tried to conserve their LPG fuel for cooking and use traditional fuels for other activities such as heating [ 30 ]. Anecdotal evidence also suggests study participants used household products that produce significant amounts of PM 2.5 , especially black carbon, during the winter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bangladesh experiences cooler temperatures in November and December, which increases traditional fuel use to heat the participant’s homes, especially evident since 29 of the 30 participants kept their traditional stoves in a separate kitchen [ 45 ]. Our survey data determined stove stacking was common as participants tried to conserve their LPG fuel for cooking and use traditional fuels for other activities such as heating [ 30 ]. Anecdotal evidence also suggests study participants used household products that produce significant amounts of PM 2.5 , especially black carbon, during the winter.…”
Section: Discussionmentioning
confidence: 99%
“…The Poriborton: The CHANge Trial feasibility study is described in Raynes-Greenow (2020) [ 30 ]. To briefly summarize, pregnant women’s exposure to HAP before and during LPG stove distribution were measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before finalising the trial design, we conducted a single-arm non-randomised feasibility study of LPG stove and cylinder distribution [ 30 ]. The findings from this study had multiple outcomes that identified issues and improved processes for conducting our trial: firstly, the development of a locally appropriate LPG cylinder supply chain in the study area, and secondly, the development of content relevant for our initial behaviour change communication such as benefits of clean cooking, practical suggestions for modifying cooking behaviours, and the important role of mothers-in-law and husbands in decision-making about cooking and fuel practices [ 30 ]. Lastly, we confirmed culturally appropriate approaches for measuring personal exposure to household air pollution and produced representative data that confirmed the LPG intervention did reduce exposure to cooking fuel emissions [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…the “plancha” improved cookstove), establishing the potential for exposure reduction, and validating measurements of exposure for carbon monoxide. Most other HAP RCTs provide relatively limited information on potential for exposure contrast at putative trial sites, instead using considerations of high HAP levels at baseline, local logistics, stove or fuel distribution feasibility, and institutional support as the primary reasons for site selection [ 15 , 24 , 36 ].…”
Section: Introductionmentioning
confidence: 99%